2007
DOI: 10.1097/01.aog.0000250901.57095.ba
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Levator Ani Muscle Defects and Function in Women With and Without Pelvic Organ Prolapse

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
416
2
20

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 614 publications
(457 citation statements)
references
References 27 publications
19
416
2
20
Order By: Relevance
“…This suggests that lower level of school education is associated with some risk factor that was not evaluated, such as socioeconomic status or nutritional status [26]. In line with our findings, previous studies have demonstrated an association between pelvic organ prolapse and lower PFM strength [25,27,28].…”
Section: Discussionsupporting
confidence: 88%
“…This suggests that lower level of school education is associated with some risk factor that was not evaluated, such as socioeconomic status or nutritional status [26]. In line with our findings, previous studies have demonstrated an association between pelvic organ prolapse and lower PFM strength [25,27,28].…”
Section: Discussionsupporting
confidence: 88%
“…On the other hand, a much greater force may be required for less displacement in women with perfect pelvic organ support, and stiffer, less elastic tissues. Our findings are consistent with those of other studies showing that TLUS and other imaging measurements of displacement may not be sensitive enough to detect structural changes of the pelvic floor [10,11,18].…”
Section: Discussionsupporting
confidence: 92%
“…Studies have shown that women in general have a reduced ability to contract the pelvic floor muscles (PFM) postpartum, but that this PFM weakness is particularly enhanced when there is a coexistent levator ani injury [9,10]. Damage to the PFM in the form of an avulsion or irreversible over-distension of the puborectalis (PR) muscle impairs the muscle function, thus increasing the risk of developing prolapse [11,12] and the risk of prolapse recurrence after surgery [13][14][15]. Not surprisingly, it is the first vaginal delivery that has the most impact on the pelvic floor [16].…”
Section: Introductionmentioning
confidence: 99%
“…Levator avulsion or ‘levator macrotrauma’ and irreversible overdistension of the hiatus or ‘levator microtrauma’ have been shown to be strong risk factors for POP development and recurrence after surgery 3 43 , 46 , 49 , 56 , 79 – 81 From a pathophysiological point of view POP can be considered a form of hernia. It is herniation of pelvic organs, be it the bladder, uterus, small or large bowel, through the levator hiatus, the hernial portal, into the vagina.…”
Section: Methodsmentioning
confidence: 99%